Evaluation of Breast Ultrasonography Findings in the Women with Dense Breasts in Mammographic Screening at Imam Reza Hospital in Mashhad, Iran (2015-2016) - Ali Feyzi; Lida Jarahi; Ali Alamdaran; Ali Abdollahi; Bita Abbasi (Mashhad University of Medical Sciences, 2018)
Introduction: Breast cancer is the most common cancer among women. Mammography is the standard method for breast cancer screening, while it has lower sensitivity in the patients with dense breasts. Therefore, women with dense breasts could be screened with other imaging modalities, such as ultrasound. The present study aimed to evaluate the ultrasonography findings in the women with dense breasts in mammography. Methods: This cross-sectional, descriptive-analytical study was conducted on all the women with dense breasts in mammogram screening at Imam Reza Hospital in Mashhad, Iran during March 2015-February 2016. Ultrasonography findings of each patient were recorded, including fibrocystic or mass changes, description of mass imaging, and sonographic BI-RADS. Data analysis was performed in SPSS version 16 using the Chi-square test at the significance level of P<0.05. Results: Among 150 patients enrolled in the study, breast ultrasonography findings were completely normal in 51 cases (34.0%) (BI-RADS 1). On the other hand, cysts or fibrocystic changes were detected in 71 patients (47.33%), four patients (2.67%) had possible benign tumors (BI-RADS 3), and possible malignant tumors (BI-RADS 4 or 5) were observed in nine cases (16.0%). Conclusion: Considering the large number of the masses detected in the ultrasound examination of the patients with dense breasts, invisibility of these tumors in mammography, and the critical role of early diagnosis in the reduction of breast cancer mortality, it is recommended that adjunct ultrasound examination be routinely performed in the patients with dense breasts on the mammogram, especially those with a positive family history of breast cancer.